Analisis Laju Pertumbuhan Kontribusi Pajak Daerah dan Pengaruhnya terhadap Pendapatan Asli Daerah Kabupaten Bogor - Syarief Gerald Prasetyo; Yustiana Wardhani (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2018)
The way to improve the authentic revenue of a district is to study its’ potential which can be used as the future financing of the development. The research methode being used is associative descriptive. As a matter of fact, based on the result of the research, it has discovered that the contribution of district’s tax on the district’s authentic revenue has been bigger on average than the other contribution of district revenues. Hotel and restaurant taxation, district taxation simultaneously have affected the district authentic revenue. Moreover, the revenue received from the taxation of hotel and restaurant, entertainment events, adverstisement, raod lighting which partially have affected the district authentic revenue accordingly. Suggestions offered are that the authority should have to perform more extensive effort on the potential district tax and to improve the awareness of the society to respect the tax obligation by giving them more training and performing more supervision of it as well as providing such the system of taxatation collection which is more effective.